2020
DOI: 10.1007/s00403-020-02156-0
|View full text |Cite
|
Sign up to set email alerts
|

Dermatological aspects of SARS-CoV-2 infection: mechanisms and manifestations

Abstract: The human infection caused by the novel SARS-CoV-2 is a public health emergency of international concern. Although the disease associated to this virus, named COVID-19, mainly affects the lungs, the infection can spread to extrapulmonary tissues, causing multiorgan involvement in severely ill patients. The broad infective capacity of SARS-CoV-2 is related to the pattern of expression of the viral entry factors ACE2 and TMPRSS2 in human tissues. As such, the respiratory and gastrointestinal tracts are at high r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 124 publications
(193 reference statements)
0
13
0
6
Order By: Relevance
“…Skin manifestations of COVID-19 patients include erythematous rashes appearing around the onset of symptoms, vesicular eruptions around the trunks and limbs, and urticaria. 17 The appearance of chilblains, or COVID toes, has also been noted. While a definite causative relationship has not been established, one study found that damage to the endothelium by the COVID-19 virus could explain the pathogenesis of COVID toes.…”
Section: Other Symptoms With Covid-19mentioning
confidence: 98%
See 1 more Smart Citation
“…Skin manifestations of COVID-19 patients include erythematous rashes appearing around the onset of symptoms, vesicular eruptions around the trunks and limbs, and urticaria. 17 The appearance of chilblains, or COVID toes, has also been noted. While a definite causative relationship has not been established, one study found that damage to the endothelium by the COVID-19 virus could explain the pathogenesis of COVID toes.…”
Section: Other Symptoms With Covid-19mentioning
confidence: 98%
“…The Southwest Respiratory and Critical Care Chronicles 2021;9(39): [15][16][17][18][19][20][21] retrospective review of 26 children with COVID toes in Italy in March-April 2020 also demonstrated that all patients recovered without any treatment. 22 In these studies and other published case reports, a variety of treatments have been used.…”
Section: Managementmentioning
confidence: 99%
“…Different authors agree that in children and young adults with suspected COVID-19 infection, reddish purple nodules have been observed on the toes, similar in appearance to pernio erythema or chilblains ("COVID toes") [15][16][17]. They also emphasize that possible dermatological complications are more common and serious in diabetic patients [18]. The distribution of these skin lesions in patients with COVID-19 is mainly located on the torso (66.7%) and the hands and feet (19.4%).…”
Section: Introductionmentioning
confidence: 94%
“…When the virus infiltrated to the central nervous system it produced neurological pathologies such as encephalitis, ictus, and polyneuropathy [18]. Neurological manifestations in the lower extremities and foot were related to Guillain-Barré syndrome associated with patients with acute symptoms of COVID-19.…”
Section: Neurological Systemmentioning
confidence: 99%
“…Offensichtlich handelt es sich um eine dysregulierte Über-aktivierung von CD8-positiven T-Lymphozyten und NK-Zellen [2], wobei eine genetische Prädisposition bezüglich der HLA-Typen diskutiert wird [3]. Zur Bewertung und Prognoseabschätzung der potenziell lebensbedrohlichen Hauterkrankung wurde der Schweregradscore SCORTEN eingeführt [4].Für die Fachgruppe Dermatologie ist der Zusammenhang von Hauterkrankungen mit einer SARS-CoV-2-Infektion zu Zeiten der Pandemie von großem Interesse und wurde ausführlich diskutiert [5,6]. In Anbetracht fehlender Rezeptorstrukturen (ACE2, TMPRSS2) als Virus-Eintrittspforten darf geschlossen werden, dass die intakte Haut nicht das Target einer Coronavirus-Infektion ist, möglicherweise jedoch die verletzte oder…”
unclassified